Simultaneous Superior Rectus Recession and Anterior Transposition of Inferior Oblique Muscle as a Surgical Option for Traumatically Lost Inferior Rectus Muscle. (3rd April 2018) - Singh, Anupam; Pandey, P. K.; Agrawal, Ajai; Rana, Kartik Maheshbhai; Mittal, S. K.; Kumar, Barun
ABSTRACT: Purpose : To evaluate the role of simultaneous superior rectus (SR) recession and anterior transposition of inferior oblique (ATIO) muscle in patients with traumatically lost inferior rectus (IR) muscle. Methods : Six patients with history of ocular trauma, followed by sudden onset vertical diplopia along with marked hypertropia (HT) and limitation of depression in abduction in the affected eye suggestive of IR disinsertion, were included in this prospective study. The patients were treated by simultaneous SR recession and ATIO muscle in the affected eye by limbal conjunctival approach under local anesthesia. Results : Preoperatively, primary position HT of 40–50 (mean 44.16 ± 4.91) prism diopters (PD) was present in all cases which increased to 65–70 (mean 65.83 ± 5.84) PD in down and in the ipsilateral gaze along with marked limitation of depression in abduction and A pattern. On exploration, the IR could not be traced in four cases. Fibrotic muscle sheath with retracted IR was found 10–12 mm away from the limbus in rest of the two patients. ATIO (6.5 mm from the limbus) with simultaneous recession of ipsilateral SR was done under local anesthesia. At 12 weeks postoperatively, three patients were orthophoric in primary position and vertical alignment with in 4–7 PD in primary position was achieved in rest of the three patients. Conclusion : Simultaneous SR recession with ATIO seems to be a good alternative to achieve satisfactory vertical alignment for patients with traumatically lost inferior rectus muscle.